Low energy consumption data acquisition systems using micro-controllers - Lee, Siang Wee. (2010)
Solar power is one of the glooming technologies that are growing in world wide, because it is a renewable energy which produced 0 carbon dioxide emission. Water and Renewable Energy Lab (WERL) is one of the research labs which are doing research on the solar power. There is solar panel on the roof top of Nanyang Technological University block S. However, because power produced by solar panel is depend of many factors like sun light, temperature etc. the power produce by solar panel need to be recorded for further research purposes. The objective of this project is to measure the current, voltage and temperature from the solar panel and store the data into database. Because the distance between WERL and the solar panel, cabling for data collecting is too expensive and troublesome, therefore in this project, a wireless transmission of data acquisition is build to serve the above purpose. This report will cover the components and circuits used as sensors to collect the data, like voltage sensor, current sensor and temperature sensor. The sensor collect the data and converted to digital form by a micro-controller unit - Zigbee module that also have the function of up to 4km wireless transmission. The final result of the project is to be able to read data directly from computer in WERL.